(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الصحية, 2019)
عُدّت التعويضات الخزفية المخبوزة على المعدن النوع الرئيسي للترميم في التعويضات الثابتة لمدة أربعين سنة وذلك لما تتمتع به من خصائص جمالية وميكانيكية جيدة. وعلى الرغم من الجهود المبذولة لزيادة قوة ارتباط الخزف بالمعدن، ما تزال الكسور الخزفية تحدث وبشكل شائع في الظروف الفموية(1,2). إن التطور الذي واكب كلاً من المواد الراتنجية وكذلك طرق تكييف السطوح المعدنية والخزفية وتهيئتها للارتباط مع الكمبوزيت جعل من استخدام الكمبوزيت الحل الأمثل لترميم كسور التعويضات الخزفية بالطريقة داخل فموية في جلسة واحدة (8). تم تحضير60 قرصاً شمعياً دائري الشكل بقطر 1 سم وسماكة املم وثم تم كسيها ومن ثم صبها بمعدن (Kera NH ) وبعد ذلك تم فرزهم إلى ثلاث مجموعات(كل منها 20 قرصاً) وفقاً لنوع الخزف المستخدم (مجموعة VMK 95، مجموعة BRICERA، مجموعة IVOCLAR ) . قسمت كل مجموعة بالتساوي إلى مجموعتين فرعيتين وفقاً لنوع نظام الترميم المستخدم في إصلاح كسور التعويضات الخزفية المعدنية على النحو الآتي: مجموعة نظام الإصلاح ceramic repair ، مجموعة نظام الإصلاح Reveneer واحتوت كل مجموعة فرعية على 10 عناصر.بعد تجهيز النموذج وضع ضمن قوالب راتنجية واخضع لتطبيق قوة قص بوساطة جهاز الاختبارات الميكانيكية العام في كلية هندسة الطيران في جامعة حلب . تم إجراء اختبار تحليل التباين أحادي الجانب ANOVA لدراسة دلالة الفروق في متوسط مقدار قوى الارتباط (بالميغاباسكال) وكان متوسط قيم قوى القص بـ MPa لمجموعة العينات (VMK95 ,BRICERA, ,IVOCLAR) لنظامCeramic repair كما يلي (4.61±0.34,9.90±2.36,11.58±2.60) على التوالي والنسبة لنظام Reveneer (5.42±0.877.72,±1.38 ،5.62±1.97) على التوالي. بينت نتائج هذه الدراسة ان قوة الربط تتأثر بنوع نظام الترميم المستخدم وكذلك بنوع الخزف إذ حقق نظام خزف ivoclar أعلى قيم مع نظام الـceramic repair في حين تفوق خزف Bricera على أنواع الخزف الأخرى مع نظام الـReveneer . The porcelain fused to metal restoration has been considered the main type of repair in the fixed prosthodontic category for forty years, for its good aesthetic and mechanical qualities. However, despite efforts to increase the strength of the bonding between the metal and the ceramic, in many cases the ceramic fractures occur in the oral cavity. Over the years, improvements were made to the risen substance and in the methods used for adjusting the metal and ceramic surfaces and their attachment to the composite. The composite has thus developed as the perfect solution for repairing fractures of ceramic. 60 round wax disks, 1mm thick and 1cm in diameter, were prepared as moulds, after which they were casted with Kera NH alloy. They were divided into three groups, each containing 20 disks, and are arranged according to the type of ceramic that was used: VMK 95, BRICERA or IVOCLAR. Each group was divided in two subgroups according to the repairing system that you use to repair the fracture of metal ceramic restorations into those two categories: Ceramic repair group and Reveener group, with each group including ten elements. After preparing the model, it was put each model into rising matrix, and they applied a share forced by the general mechanical testing machine in the Faculty of Aviation Engineering in the University of Aleppo. ANOVA has been applied to study the differences between the means of the bonding forces in megapixels and the means of the share strength with MPa for a group of samples (IVOCLAR, VMK 95, BRICERA). For the ceramic repair system, it was the following: (4.61±0.34,9.90±2.36,11.58±2.60) respectively. For the Reveener system, (5.42±0.87,7.72±1.38,5.62±1.97). The results of this study showed that the bonding strength was affected according to what restoration system was used as well as the type of ceramic employed.